Fuzzy pid control for indoor CO2 concentration - Sun, Xuan (2016)
In this research work, a fuzzy PID controller is proposed to realize C02-based DCV, rather than traditional PID controller frequently applied in building controls. On the basis of DCV, the fresh air flow rate is calculated through the C02 mass balance equation to meet the indoor C02 concentration requirements. Fuzzy PID strategy initially uses classic PID control with three parameters tuned by experience. During the process of system operating, those parameters are tuned by three fuzzy modules according to the practical environment around. To get specific results, simulation models of PID, pure fuzzy and fuzzy PID controller are built in Simulink. The response graphics show that fuzzy PID has faster response speed than PID and much smaller steady-state error than pure fuzzy. Besides, it achieves best energy savings performance among them. Therefore, fuzzy PID controller can achieve acceptable C02 level with minimum energy consumption. In addition, this thesis also introduces using single chip to achieve the controlling procedures of AHU start and stop.